PENGUSAHA WARUNG TEGAL DI JAKARTA (Pendekatan Modal Sosial) - Rinda Asytuti (Jurnal Hukum Islam, 2015)
Warung Tegal (Warteg) is an example of local based small and medium enterprises, of which the owners are coming from a local town called Tegal. While the town of Tegal, where such restaurants originally come from, has its own distinctive culture, Warung Tegal are closely linked with urban migrant culture of Jakarta. Warteg is not only a place to suffice people needs of having meals but also as a place for people to share and discuss stories and information from daily life up to political issues. On the other hand, this small enterprise is not individually owned, but rather it is owned and developed by families in turns. I found the social modal factor within Warteg owners is interesting to be further researched. This study aims at finding out the level of social modal among Warteg owners in Jakarta. The quantitative approach to measure social modal based on the variables of cohesion, trust, norms and economic empowering networking were employed in this research. The result of this study showed that there was a significant correlation of 54.8 % between social modal variables, which included cohesion, trust, norms and networking, and Warteg economic development. Additionally, the result of the study also indicated that cohesion level and networking factor were the most significant factors influencing the economic development of Warteg in Jakarta.